Machine cell formation using simulated annealing algorithm in cellular manufacturing system. (2018) - Adinarayanan, A.; Uthayakumar, M.; Prabhakaran, G.
Group technology is a production strategy and it has the ability to get solution for certain problems of complexity and long manufacturing lead times in batch manufacturing. This can be achieved by using a systematic method of equipments into machine cells and components into part families, based on the suitable similarity criteria. The present work deals with the machine cell formation problem with the aim of minimising the aggregate cell load variation and aggregate inter cellular move. The quantity of parts, operation sequences, processing time, capacity of machines, and workload of machineries were considered as parameters. In order to group the machineries, one of the metaheuristic search methodologies the simulated annealing (SA) algorithm is considered. For computational processing 40 machines and 100 part types are being used. From the findings it is observed that, in most of the literature problems SA provides better result than that of other methods in the literature and in few cases it yields equal result to the best one of the other methods.